The Foundation of the Third Renaissance is a Spiritual Ascent - Botirova Sayyora (Research Parks Publishers, 2021)
spirituality is such a factor that determines the development of society, the perfection of people and nation and the perfection of personality, is the value that gives Man the essence and essence of humanity, elevates a person from Earth to heaven, encourages him to goodness. The absence of a branch of Hech, which is not directly related to the spirituality of science, is a fact that does not require proof.